Phosphogypsum-based phase change unfired ceramsite, preparation method thereof and application of ceramsite in phase change-reinforcement-solidification co-treatment of sludge

Through the coordinated disposal technology of phosphogypsum-based cinnamons and phase change materials, the curing problem of high moisture content and high organic matter silt is solved, efficient solidification of silt and the resource utilization of diversified solid waste are achieved, and environmental pressure and cost are reduced. .

CN119219352APending Publication Date: 2024-12-31HOHAI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411338664.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively treat sludge with high moisture content and high organic matter, resulting in limited curing effect and high cost. Multiple solid wastes such as phosphogypsum, fly ash and calcium carbide waste slag have not been fully utilized, and the traditional ceramic preparation process is consumed. A lot of heat energy and a large environmental pressure.

Method used

The phosphogypsum-based non-burning ceramics are used to prepare ceramics through phosphogypsum, fly ash, calcium carbide slag and hydrogen peroxide. Combined with phase change materials, the sludge is treated in a coordinated manner through phase change-reinforcement-curing to improve the curing effect of the sludge. and resource utilization.

Benefits of technology

It realizes effective curing of high moisture content and high organic matter silt, reduces curing costs, improves the strength and insulation properties of the ceramite, promotes the resource utilization of diversified solid waste, and reduces environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219352A_ABST
    Figure CN119219352A_ABST
Patent Text Reader

Abstract

The invention discloses ardealite-based phase change unfired ceramsite, a preparation method thereof and application of the ardealite-based phase change unfired ceramsite in phase change-reinforcement-solidification co-treatment of sludge, and belongs to the field of sludge solidification. The ardealite-based unfired ceramsite comprises the following raw materials: ardealite, fly ash, carbide slag, vermiculite, hydrogen peroxide and water. The invention also provides ardealite-based phase-change unfired ceramsite and a preparation method thereof, and also discloses solidified sludge doped with the ardealite-based phase-change unfired ceramsite, which is prepared by using the ardealite-based phase-change unfired ceramsite. The invention further provides a method for co-processing the high-water-content and high-organic-matter sludge through phase change-reinforcement-solidification, the method is simple in process and low in cost, a large amount of various solid waste is applied, and the prepared solidified sludge can be applied to various environment-friendly and energy-saving construction scenes such as damming, canal repairing and sunlight greenhouses.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sludge solidification, and in particular relates to a phosphogypsum-based phase-change unfired ceramsite and a preparation method thereof, and an application thereof in the phase-change-reinforcement-solidification coordinated treatment of sludge. Background Art

[0002] Phosphogypsum is a byproduct of the wet process of phosphoric acid production in industry. Every ton of phosphate fertilizer produced will produce 4 to 5 tons of phosphogypsum. It is a typical bulk solid waste in the chemical industry. Large-scale storage causes serious environmental pollution. The main components of phosphogypsum are dihydrate gypsum (CaSO4·2H2O) and hemihydrate gypsum (CaSO4·1 / 2H2O). It is an acidic waste with very poor plasticity. At present, it is urgent to effectively treat phosphogypsum. One of the disposal methods for phosphogypsum at home and abroad is on-site greening of the yard. This method realizes the safe on-site disposal and ecological management of bulk industrial solid waste, but it only alleviates the pollution problem of phosphogypsum. The long-term storage of phosphogypsum is still an environmental hazard. Another disposal method is the resource utilization of phosphogypsum, which is mainly used as a cement retarder, external supply and sale, building materials, road construction materials, soil conditioners, sulfuric acid production, etc. The annual utilization accounts for about 45% to 55% of the total annual emissions. Therefore, in general, phosphogypsum has not been effectively utilized in large quantities, and the current status of phosphogypsum as a major solid waste has not been alleviated.

[0003] Fly ash is solid waste discharged from coal-fired power plants and is the largest source of solid waste pollution in China. With the development of coal-fired power generation, the emission of fly ash has increased year by year. Large amounts of fly ash stockpiles not only occupy land, but also pose a serious threat to surrounding water and soil. In addition, the comprehensive utilization rate of fly ash is currently low, and the comprehensive utilization technology and level are also relatively low, mainly in cement additives, building materials processing, and concrete addition. Therefore, the resource utilization and high value-added utilization of fly ash have become pain points, and it is imperative to develop new high-value downstream products and expand the application field.

[0004] Calcium carbide waste residue is the waste residue with calcium hydroxide as the main component after acetylene gas is obtained by hydrolysis of calcium carbide. In industry, 1 ton of calcium carbide plus water can generate more than 300 kilograms of acetylene gas, and at the same time generate 10 tons of industrial waste liquid with a solid content of about 12%, which is commonly known as calcium carbide slag slurry. The traditional large-scale utilization of calcium carbide slag is mainly to replace limestone to prepare cement and other construction materials, but its development is limited due to the saturation of the domestic market and the concentrated geographical location. With the continuous development of the chlor-alkali industry, the large-scale discharge and accumulation of calcium carbide slag are increasing, and the pollution to the environment and the consumption of land resources are also increasing.

[0005] Silt is an object that is deposited elsewhere due to water movement. It contains high levels of organic matter and heavy metals, and has a very high water content. It is a waste generated during the dredging of rivers and lakes. At present, the main method for treating silt is to use landfill to relieve the pressure on the environment. The accumulated silt will not only occupy more land resources, but also contain harmful components such as heavy metals (copper, chromium, arsenic, mercury, cadmium, etc.), organic pollutants and odor, which seriously endanger biological reproduction and human health, becoming another major public hazard. Zhang Chunlei et al. studied the effect of initial moisture content on the effect of cement solidification of silt. When the water content in the silt exceeds the amount of water required for cement hydration, the excess water is distributed in the middle of the solidified silt as pores, which reduces the strength of the solidified silt. The results show that the strength of the solidified silt decreases in a power form with the increase of the initial moisture content. Fan Zhaoping and others studied the effect of organic matter content on sludge solidification. The results showed that when the organic matter content of sludge is less than 4.3%, every 1% increase in organic matter content will lead to a 25-30% strength loss in the solidified sludge. In short, due to the high moisture content and organic matter content of sludge, the solidification effect of sludge solidification in the existing technology is severely restricted, and the solidification cost is also relatively high.

[0006] Ceramic granules are a kind of lightweight ceramic material, which mostly appear as round or elliptical spheres, or irregular gravel. Its surface is a hard shell with a certain strength; the interior is porous and has a certain adsorption capacity. Ceramic granules are currently used to replace crushed stone and gravel in concrete, and are also used for sewage treatment, gardening and other purposes. Traditional ceramsite preparation is usually sintered from materials such as clay, shale, and cement, which requires natural resources such as high-quality clay, and consumes a lot of heat energy during the firing process, emitting a large amount of CO2, which greatly increases environmental pressure and runs counter to the principle of sustainable development.

[0007] Phase change material (hereinafter referred to as PCM) refers to a material that changes its phase state (i.e. phase change, which has three forms: solid-solid, solid-liquid, and solid-gas) within the phase change temperature range to absorb, store or release a large amount of heat in the form of latent heat while keeping its own temperature unchanged. Currently, phase change materials have been widely used in many energy storage and temperature control fields such as solar energy utilization, building thermal insulation, and battery thermal management. However, due to considerations such as leakage prevention and environmental pollution prevention, phase change capsules are often used in actual projects. The disadvantages are reflected in: on the one hand, the product price is relatively high, and the cost of engineering use is high; on the other hand, the packaging material of the phase change capsule has a great influence on the heat exchange efficiency during the PCM phase change process.

[0008] Therefore, how to provide a method that can combine phase change expanded clay materials and multiple solid waste raw materials such as phosphogypsum, fly ash, carbide slag and sludge to improve the solidification effect of high-water content and high-organic matter sludge is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0009] In order to solve the above technical problems, the present invention proposes a phosphogypsum-based unfired ceramsite, a phosphogypsum-based phase-change unfired ceramsite, and a preparation method thereof, and an application thereof in the phase-change-reinforcement-solidification coordinated treatment of sludge. To achieve the above objectives, the present invention provides the following technical solutions:

[0010] A phosphogypsum-based unfired ceramsite, comprising the following raw materials in parts by weight:

[0011] 30-45 parts of phosphogypsum, 13-18 parts of fly ash, 13-18 parts of carbide slag, 5-10 parts of vermiculite, 4 parts of hydrogen peroxide and 20 parts of water.

[0012] Preferably, the phosphogypsum is a byproduct solid waste of industrial wet production of phosphoric acid, has a pH value greater than 3.0, and has a phosphogypsum fineness of not less than 0.42 mm.

[0013] Furthermore, the fly ash is primary fly ash.

[0014] Furthermore, the carbide slag is a waste solid with calcium hydroxide as the main component.

[0015] Furthermore, the mass concentration of the hydrogen peroxide is 30%.

[0016] Beneficial effects: The present invention selects phosphogypsum as the main material to give full play to its gelling effect, wherein the main components of phosphogypsum are calcium sulfate and calcium sulfate hemihydrate, wherein the calcium ions react with silicon-containing substances to generate calcium silicate, which makes the expanded clay produce strength.

[0017] The present invention uses fly ash as the active material to provide the basic strength required by ceramsite. The chemical composition of fly ash is mainly SiO2 and Al2O3, which is a good active gelling material. In an alkaline environment, it can destroy the relatively stable glass network structure in fly ash, so that the active components SiO2 and Al2O3 contained therein are dissolved and then react with Ca 2+ The reaction occurs to generate calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH) hydraulic cementitious products, thereby increasing the strength of the ceramsite.

[0018] The present invention uses carbide slag as an alkaline activator. Since the glass structure in fly ash limits its potential activity, it needs to be fully released in an alkaline environment. The Ca(OH)2 contained in carbide slag can provide an alkaline environment and the Ca(OH)2 required by the reaction system. 2+ .

[0019] The present invention selects hydrogen peroxide as a foaming agent. During the preparation of ceramsite, oxygen generated by the decomposition of hydrogen peroxide can generate a large number of bubbles in the colloid of the cementitious material, so that stable gaps are formed in the finished ceramsite, thereby improving the porosity and thermal insulation performance of the unfired ceramsite.

[0020] A method for preparing phosphogypsum-based unfired ceramsite comprises the following steps:

[0021] The phosphogypsum, carbide slag and vermiculite are ground and mixed with fly ash, and a mixed solution of hydrogen peroxide and water is sprayed while stirring. The mixture is then granulated, aged, microwave irradiated and steam cured to obtain phosphogypsum-based unfired ceramsite.

[0022] Preferably, the powder needs to be sieved through an 80-mesh sieve after grinding.

[0023] Preferably, dehydration is required before the grinding, and the dehydration is mechanical dehydration, and the dehydration is performed to a moisture content of less than 55%.

[0024] The granulation is to produce raw granules with a particle size of 5 to 20 mm.

[0025] Preferably, the aging temperature is room temperature and the time is 2 to 4 hours;

[0026] Beneficial effects: The purpose of aging is to ensure the bonding of phosphogypsum with other materials, promote the growth of ceramsite strength, and prevent the raw granules from losing moisture too quickly and causing cracking. During the aging process, the active substances in the fly ash and the alkali-activated materials (carbide slag) fully react with volcanic ash to generate calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH) hydraulic cementitious products, thereby increasing the strength of ceramsite.

[0027] Among them, the main reactions of volcanic ash reaction are as follows:

[0028] 3CaO·SiO2+nH2O=xCaO·SiO2·yH2O+(3-x)Ca(OH)2 (1)

[0029] 2CaO·SiO2+nH2O=xCaO·SiO2·yH2O+(2-x)Ca(OH)2 (2)

[0030] 3CaO·Al2O3+6H2O=3CaO·Al2O3·6H2O (3)

[0031] xCa(OH)2+Al2O3+(n-1)H2O=xCaO·Al2O3·nH2O (4)

[0032] xCa(OH)2+SiO2+(n-1)H2O=xCaO·SiO2·nH2O (5)

[0033] CaSO4·2H2O+3CaO·Al2O3+12H2O=3CaO·Al2O3·CaSO4·14H2O (6)

[0034] Preferably, the microwave irradiation power is 480W and the time is 3min;

[0035] Beneficial effects: The purpose of microwave irradiation is to promote the escape of moisture to create open gaps and maximize the water absorption rate of the finished ceramsite.

[0036] Preferably, the steam curing temperature is 120-140° C., and the time is not less than 2 days.

[0037] A method for preparing phosphogypsum-based phase-change unfired ceramsite comprises the following steps:

[0038] The phosphogypsum-based unfired ceramsite is immersed in a liquid phase change material, filtered, and allowed to stand in an environment below the phase change temperature to obtain the phosphogypsum-based phase change unfired ceramsite.

[0039] Preferably, the phase change material is paraffin (a mixture of alkanes such as n-tetradecane and n-heptadecane) and / or an inorganic hydrated salt;

[0040] The inorganic hydrated salt is calcium chloride hexahydrate (CaCl2·6H2O).

[0041] Preferably, before the soaking, the process further comprises drying the phosphogypsum-based unfired ceramsite and placing it in a reactor and then vacuuming to remove air.

[0042] More preferably, the vacuuming is performed at a negative pressure of 0 to 10 kPa, and the vacuuming is continued for 5 minutes after reaching the set negative pressure.

[0043] Preferably, the soaking specifically comprises the following steps:

[0044] Under a vacuum environment with a negative pressure of 50 to 80 kPa, the ceramsite is immersed in an excess of liquid phase change material for 0.5 to 2 hours, and then the vacuum state is eliminated to normal pressure, and the immersion is continued for 30 minutes.

[0045] Preferably, the environment below the phase transition temperature is 15 to 20° C. below the phase transition temperature;

[0046] The standing time is 10 to 30 minutes.

[0047] Beneficial effects: The present invention uses ceramsite as the storage medium of phase change material. Ceramsite has the characteristics of high porosity and strong adsorption, and is suitable for long-term storage of liquid phase change material. In addition, the internal pore structure of ceramsite divides the phase change material into small pieces, which greatly increases the phase change heat transfer efficiency of the phase change material; at the same time, the thermal conductivity of the ceramsite pore structure skeleton is also relatively good. Therefore, the phase change ceramsite product obtained has the advantages of low cost, long-term stable energy storage performance, and high heat exchange efficiency in the phase change process.

[0048] The above-mentioned phosphogypsum-based unfired ceramsite has a water absorption rate of 12-15% in 1 hour and a bulk density of 400-600 kg / m 3 , the cylinder pressure strength is 4~6MPa.

[0049] A solidified sludge mixed with phosphogypsum-based phase-change unfired ceramsite comprises the phosphogypsum-based phase-change unfired ceramsite.

[0050] Preferably, the following raw materials are included in parts by weight:

[0051] 60-80 parts of sludge, 0.1 parts of potassium ferrate, 2.0-3.6 parts of cement, 1.3-2.9 parts of phosphogypsum and 15-35 parts of the phosphogypsum-based phase-change unfired ceramsite.

[0052] Preferably, the sludge has a water content of 50% and an organic matter content of 5%.

[0053] Preferably, the cement is PO42.5 ordinary Portland cement, which is used at 5-15% of the dry soil mass in the sludge, and the phosphogypsum is used at 20-40% of the cement dosage.

[0054] Beneficial effects: The present invention uses ordinary Portland cement as a curing agent. As the cement is added to the sludge with high water content and high organic matter content, the cement undergoes a hydration reaction and gradually generates calcium silicate hydrate (CSH). The calcium silicate hydrate is bonded together with the soil particles, eventually causing the strength of the solidified sludge to increase.

[0055] The present invention uses potassium ferrate as an oxidant. On the one hand, potassium ferrate oxidizes organic matter in the sludge, destroys functional groups such as carboxyl and phenolic hydroxyl groups of the organic matter, and reduces the Ca generated during the hydration process of organic matter and cement. 2+ 、Al 3+ Complexation occurs to ensure the full progress of cement hydration reaction; on the other hand, potassium ferrate itself is reduced by organic matter, Fe(VI) is reduced to Fe(III), and the high-valent cation Fe 3+ By exchanging with the low-valent cations on the surface of the soil particles, the thickness of the diffusion layer is reduced to a certain extent, causing the soil particles themselves to flocculate and improving the strength of the solidified silt.

[0056] The role of the above-mentioned phosphogypsum is to provide Ca 2+ and SO42- , promoting the formation of calcium sulfonate, which can then fill the gaps between soil particles and improve the strength of solidified sludge. In addition, the hemihydrate gypsum (CaSO4·1 / 2H2O) in the phosphogypsum component can absorb part of the free water in the sludge and reduce the moisture content of the sludge.

[0057] The phosphogypsum-based phase-change unfired ceramsite prepared by the present invention has the characteristic of high water absorption. By utilizing this characteristic, the phosphogypsum-based phase-change unfired ceramsite is added to the sludge to absorb free water in the sludge, thereby further reducing the water content of the sludge.

[0058] Furthermore, because the phase change material adsorbed in the phosphogypsum-based phase change unfired expanded clay has the characteristics of phase change energy storage and heat release, no significant frost heave, and reversible phase change process, after the solidified soil is filled into the interior of the building, it can generate a large amount of latent heat through the transformation between the solid phase and liquid phase of the phase change material, regulate the temperature field within a certain range inside and around the building, and ultimately reduce the peak temperature change of the building.

[0059] A method for phase change-reinforcement-solidification coordinated treatment of high-water content and high-organic matter sludge, using the above raw materials, specifically comprising the following steps:

[0060] The sludge is mixed with potassium ferrate and allowed to stand for pretreatment for 24 hours. It is then evenly mixed with cement, phosphogypsum powder and phosphogypsum-based phase-change unfired ceramsite and allowed to stand for curing to obtain solidified sludge mixed with phosphogypsum-based phase-change unfired ceramsite, thus completing the phase change-reinforcement-solidification coordinated treatment of high-water content and high-organic matter sludge.

[0061] Preferably, the temperature of the static curing is room temperature, and the relative humidity is not less than 90%, so as to ensure sufficient hydration reaction of the cement.

[0062] Beneficial effect: The present invention provides a phase change-reinforcement-solidification coordinated treatment method for sludge, and its object is sludge with high water content and high organic matter. The basic method is to use phase change ceramsite to carry out phase change-reinforcement-solidification combined treatment of sludge. Reinforcement in the present invention refers to adding ceramsite to the sludge matrix during solidification, which belongs to the particle reinforcement method. Particle reinforcement is a concept in composite material mechanics, which refers to a reinforcement method in which a certain number of particles are mixed in the matrix material, and the mechanical properties of the entire material are improved through the interaction between the particles and the matrix.

[0063] The phase change described in the present invention is to utilize PCM within its phase change temperature range to absorb or release a large amount of heat through the transition between different phases, thereby regulating the temperature field inside the building, and ultimately generating engineering benefits or economic benefits.

[0064] The solidification of the sludge described in the present invention, on the one hand, utilizes potassium ferrate to oxidize the organic matter contained in the sludge to reduce the organic matter content, and on the other hand, utilizes the water absorption of expanded clay and the hemihydrate calcium sulfate in the phosphogypsum to absorb a certain amount of water to reduce the moisture content, and the two aspects work together to improve the sludge solidification effect.

[0065] The present invention proposes a phase change-reinforcement-solidification method for the coordinated treatment of high-water content and high-organic matter sludge, which includes the raw material composition and preparation of phosphogypsum ceramsite and phase change ceramsite, and also involves the processes of reinforcement and strengthening with ceramsite, phase change temperature regulation and sludge solidification. The solidified sludge finally obtained by the above method can have a 7d unconfined compressive strength of 0.8MPa.

[0066] Application of solidified sludge of phosphogypsum-based phase-change unfired ceramsite in the field of construction.

[0067] Preferably, the applications include anti-seepage materials for core walls of high dams in high-cold areas, wall materials for agricultural greenhouses and solar greenhouses, and cushion materials for lining channels.

[0068] Compared with the prior art, the present invention has the following advantages and technical effects:

[0069] The present invention is based on the preparation of phosphogypsum-based phase-change unfired ceramsite, and for the first time proposes a sludge resource utilization approach of "phase change-reinforcement-solidification" coordinated disposal. For the "phase change" function, the present invention makes full use of the high adsorption characteristics of ceramsite to adsorb PCM, so as to realize the function of solidified sludge of phosphogypsum-based phase-change unfired ceramsite in the fields of building energy conservation, temperature adjustment and antifreeze, and reduce the cost of using PCM in engineering; for the "reinforcement" function, the present invention adds ceramsite to the solidified sludge matrix to perform particle reinforcement and reinforcement, and improves the strength performance of sludge materials as a whole through the interaction between particles and the matrix; for the "solidification" function, the present invention simultaneously utilizes ceramsite water absorption and semi-hydrated gypsum to reduce the water content of dredged sludge, and uses potassium ferrate to reduce the influence of organic matter in sludge on the sludge solidification effect, thereby reducing the solidification cost of high-water-content and high-organic sludge. It provides an energy-saving and environmentally friendly approach for large-scale resource utilization of various solid wastes such as phosphogypsum and sludge. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0071] Figure 1 This is the production process flow chart of phosphogypsum-based phase-change unfired ceramsite;

[0072] Figure 2 This is a schematic diagram of the production principle of phosphogypsum-based phase-change unfired ceramsite;

[0073] Figure 3 This is a schematic diagram of the application of solidified sludge as a core wall dam anti-seepage material in Application Example 1 of the present invention;

[0074] Figure 4 This is a schematic diagram of the application of solidified sludge as a solar greenhouse wall material in Application Example 2 of the present invention;

[0075] Figure 5 This is a schematic diagram of the application of solidified sludge as a channel lining cushion material in Application Example 3 of the present invention;

[0076] Figure 6 It is a schematic diagram comparing the temperature change process lines when the solidified sludge obtained in Example 4 and Comparative Example 1 is used respectively on the joint surface of new and old materials during the construction period of a high dam in a high-cold region in Application Example 1 of the present invention;

[0077] Figure 7 This is a schematic diagram showing the comparison of the temperature versus depth Z curves when the solidified sludge obtained in Example 4 and Comparative Example 1 are used as the cold region channel cushion in Application Example 3 of the present invention;

[0078] Figure 8 It is a schematic diagram comparing the air temperature change process lines when the solidified sludge obtained in Example 8 and Comparative Example 1 are used respectively during the use period of the agricultural greenhouse solar greenhouse in Application Example 2 of the present invention. DETAILED DESCRIPTION

[0079] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0080] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0081] The raw materials in the examples of the present invention are all purchased from commercial sources.

[0082] Among them, phosphogypsum is a byproduct solid waste of industrial wet production of phosphoric acid, with a pH value greater than 3.0 and a phosphogypsum fineness of not less than 0.42 mm;

[0083] The fly ash is first-grade fly ash;

[0084] Carbide slag is a waste solid with calcium hydroxide as the main component;

[0085] The mass concentration of hydrogen peroxide is 30%;

[0086] The cement is P·O42.5 ordinary Portland cement;

[0087] The silt can be dredged from nearby rivers and lakes, or the riverbed mud can be used locally.

[0088] The "parts" in the embodiments of the present invention refer to parts by weight.

[0089] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.

[0090] Example 1

[0091] A phosphogypsum-based unfired ceramsite, comprising the following raw materials in parts by weight:

[0092] 30 parts of phosphogypsum, 18 parts of fly ash, 18 parts of carbide slag, 10 parts of vermiculite, 4 parts of hydrogen peroxide, and 20 parts of water.

[0093] A method for preparing phosphogypsum-based unfired ceramsite, such as Figure 1 As shown, using the above-mentioned raw materials of phosphogypsum-based unfired ceramsite, the following steps are included:

[0094] (1) mechanically dehydrating phosphogypsum, carbide slag and vermiculite (to a moisture content of less than 55%), drying to constant weight, grinding and passing through an 80-mesh sieve to obtain phosphogypsum powder, carbide slag powder and vermiculite powder;

[0095] (2) mixing hydrogen peroxide and water to obtain a mixed solution, then putting the above-mentioned phosphogypsum powder, carbide slag powder, vermiculite powder and fly ash into a mixing barrel, spraying the mixed solution of hydrogen peroxide and water while stirring, stirring to form a mixture, and then transferring the mixture to a pelletizing device, adjusting the amount of water to pelletize, and obtaining green pellets with a particle size of 10 mm;

[0096] (3) the raw granules were then aged at room temperature for 3 h, microwave irradiated at 480 W for 3 min, and steam cured (temperature of 120° C. for 2 d) to obtain phosphogypsum-based unfired ceramsite;

[0097] (4) Conduct performance tests on phosphogypsum-based unfired expanded clay.

[0098] Example 2

[0099] A phosphogypsum-based unfired ceramsite, comprising the following raw materials in parts by weight:

[0100] 38 parts of phosphogypsum, 15 parts of fly ash, 15 parts of carbide slag, 8 parts of vermiculite, 4 parts of hydrogen peroxide, and 20 parts of water.

[0101] A method for preparing phosphogypsum-based unfired ceramsite, using the above-mentioned raw materials of phosphogypsum-based unfired ceramsite, and other process steps and parameters are the same as those in Example 1.

[0102] Example 3

[0103] A phosphogypsum-based unfired ceramsite, comprising the following raw materials in parts by weight:

[0104] 45 parts of phosphogypsum, 13 parts of fly ash, 13 parts of carbide slag, 5 parts of vermiculite, 4 parts of hydrogen peroxide, and 20 parts of water.

[0105] A method for preparing phosphogypsum-based unfired ceramsite, using the above-mentioned raw materials of phosphogypsum-based unfired ceramsite, and other process steps and parameters are the same as those in Example 1.

[0106] Example 4

[0107] A phosphogypsum-based phase-change unfired ceramsite comprises the following raw materials: ceramsite and excess phase-change material.

[0108] The ceramsite is the phosphogypsum-based unfired ceramsite obtained in Example 2, the phase change material is n-tetradecane, and the phase change latent heat is 193 kJ / kg.

[0109] A method for preparing phosphogypsum-based phase-change unfired ceramsite, such as Figure 1 As shown, using the above-mentioned raw materials of phosphogypsum-based phase-change unfired ceramsite, the process includes the following steps:

[0110] (1) The phosphogypsum-based unfired ceramsite obtained in Example 2 was dried at 100° C. for 2 h, placed in a reactor, and evacuated to a negative pressure of 5 kPa and then continued to evacuate for 5 min to remove air from the phosphogypsum-based unfired ceramsite;

[0111] (2) The phosphogypsum-based unfired ceramsite after air removal is soaked in an excess of liquid n-tetradecane for 1 hour under a vacuum environment with a negative pressure of 50 kPa, and then the vacuum state is eliminated and naturally restored to normal pressure, and the soaking is continued for 30 minutes to prevent the phase change material from escaping during the process of restoring normal pressure. After the soaking is completed, the filter is filtered and the filter cake is allowed to stand at -15°C for 30 minutes to allow the phase change material adsorbed by the phosphogypsum-based unfired ceramsite to become a solid, and then transferred to a storage container to obtain the phosphogypsum-based phase change unfired ceramsite.

[0112] A solidified sludge of phosphogypsum-based phase-change unfired ceramsite, comprising the following raw materials in parts by weight:

[0113] 75 parts of sludge (water content 50%, organic matter content 5%), 0.1 parts of potassium ferrate, 3.6 parts of cement, 1.3 parts of phosphogypsum, and 20 parts of the above-mentioned phosphogypsum-based phase-change unfired ceramsite;

[0114] A phase change-reinforcement-solidification method for co-disposing high-water content and high-organic matter sludge, using the above-mentioned phosphogypsum-based phase change unfired ceramsite solidified sludge raw material, comprises the following steps:

[0115] (1) adding potassium ferrate to the sludge, stirring thoroughly, and standing for pretreatment for 24 hours to obtain a mixture A;

[0116] (2) mechanically dehydrating and drying the phosphogypsum to constant weight, then grinding and passing through an 80-mesh sieve to prepare powder B;

[0117] (3) Cement, powder B and phosphogypsum-based phase-change unfired ceramsite are added to the mixture A, stirred evenly, and then allowed to stand for curing at room temperature and a relative humidity of not less than 90% to ensure that the cement is fully hydrated to obtain solidified sludge mixed with phosphogypsum-based phase-change unfired ceramsite.

[0118] (4) Conducting performance testing on solidified sludge.

[0119] Example 5

[0120] A phosphogypsum-based phase-change unfired ceramsite, whose raw material composition is the same as that of Example 4.

[0121] A method for preparing phosphogypsum-based phase-change unfired ceramsite, using the above-mentioned raw materials of phosphogypsum-based phase-change unfired ceramsite, and other process steps and parameters are the same as those in Example 4.

[0122] A solidified sludge mixed with phosphogypsum-based phase-change unfired ceramsite, using the phosphogypsum-based phase-change unfired ceramsite, comprising the following raw materials in parts by weight:

[0123] 75 parts of sludge (water content 50%, organic matter content 5%), 0.1 parts of potassium ferrate, 2.0 parts of cement, 2.9 parts of phosphogypsum, and 20 parts of the above-mentioned phosphogypsum-based phase-change unfired ceramsite.

[0124] A phase change-reinforcement-solidification method for the coordinated treatment of high-water content and high-organic matter sludge uses the above-mentioned phosphogypsum-based phase change unfired ceramsite as a raw material for solidified sludge, and other process steps and parameters are the same as those in Example 4.

[0125] Example 6

[0126] A phosphogypsum-based phase-change unfired ceramsite, whose raw material composition is the same as that of Example 4.

[0127] A method for preparing phosphogypsum-based phase-change unfired ceramsite, using the above-mentioned raw materials of phosphogypsum-based phase-change unfired ceramsite, and other process steps and parameters are the same as those in Example 4.

[0128] A solidified sludge mixed with phosphogypsum-based phase-change unfired ceramsite, using the phosphogypsum-based phase-change unfired ceramsite, comprising the following raw materials in parts by weight:

[0129] 60 parts of sludge (water content 50%, organic matter content 5%), 0.1 parts of potassium ferrate, 3.6 parts of cement, 1.3 parts of phosphogypsum, and 35 parts of the above-mentioned phosphogypsum-based phase-change unfired ceramsite.

[0130] A phase change-reinforcement-solidification method for the coordinated treatment of high-water content and high-organic matter sludge uses the above-mentioned phosphogypsum-based phase change unfired ceramsite as a raw material for solidified sludge, and other process steps and parameters are the same as those in Example 4.

[0131] Example 7

[0132] A phosphogypsum-based phase-change unfired ceramsite, whose raw material composition is the same as that of Example 4.

[0133] A method for preparing phosphogypsum-based phase-change unfired ceramsite, using the above-mentioned raw materials of phosphogypsum-based phase-change unfired ceramsite, and other process steps and parameters are the same as those in Example 4.

[0134] A solidified sludge mixed with phosphogypsum-based phase-change unfired ceramsite, using the phosphogypsum-based phase-change unfired ceramsite, comprising the following raw materials in parts by weight:

[0135] 80 parts of sludge (water content 50%, organic matter content 5%), 0.1 parts of potassium ferrate, 3.6 parts of cement, 1.3 parts of phosphogypsum, and 15 parts of the above-mentioned phosphogypsum-based phase-change unfired ceramsite.

[0136] A phase change-reinforcement-solidification method for the coordinated treatment of high-water content and high-organic matter sludge uses the above-mentioned phosphogypsum-based phase change unfired ceramsite as a raw material for solidified sludge, and other process steps and parameters are the same as those in Example 4.

[0137] Example 8

[0138] A phosphogypsum-based phase-change unfired ceramsite comprises the following raw materials: ceramsite and excess phase-change material.

[0139] The ceramsite is the phosphogypsum-based unfired ceramsite prepared in Example 2, the phase change material is n-heptadecane, and the phase change latent heat is 227 kJ / kg.

[0140] A method for preparing phosphogypsum-based phase-change unfired ceramsite, such as Figure 1 As shown, using the above-mentioned raw materials of phosphogypsum-based phase-change unfired ceramsite, the process includes the following steps:

[0141] (1) The phosphogypsum-based unfired ceramsite obtained in Example 2 was dried at 100° C. for 2 h, placed in a reactor, and evacuated to a negative pressure of 5 kPa and then continued to evacuate for 5 min to remove air from the phosphogypsum-based unfired ceramsite;

[0142] (2) Under a vacuum environment with a negative pressure of 50 kPa, the phosphogypsum-based unfired ceramsite after air removal is soaked in an excess of liquid n-heptadecane for 1 hour, and then the vacuum state is eliminated and naturally restored to normal pressure, and the soaking is continued for 30 minutes to prevent the phase change material from escaping during the process of restoring normal pressure. After the soaking is completed, the filter cake is left to stand at 0°C for 30 minutes to allow the phase change material adsorbed by the phosphogypsum-based unfired ceramsite to become a solid, and then transferred to a storage container to obtain the phosphogypsum-based phase change unfired ceramsite.

[0143] A solidified sludge of phosphogypsum-based phase-change unfired ceramsite, comprising the following raw materials in parts by weight:

[0144] 75 parts of sludge (water content 50%, organic matter content 5%), 0.1 parts of potassium ferrate, 3.6 parts of cement, 1.3 parts of phosphogypsum, and 20 parts of the above-mentioned phosphogypsum-based phase-change unfired ceramsite.

[0145] A phase change-reinforcement-solidification method for the coordinated treatment of high-water content and high-organic matter sludge uses the above-mentioned phosphogypsum-based phase change unfired ceramsite as a raw material for solidified sludge, and other process steps and parameters are the same as those in Example 4.

[0146] Example 9

[0147] A phosphogypsum-based phase-change unfired ceramsite, whose raw material composition is the same as that of Example 8.

[0148] A method for preparing phosphogypsum-based phase-change unfired ceramsite, using the above-mentioned raw materials of phosphogypsum-based phase-change unfired ceramsite, and other process steps and parameters are the same as those in Example 8.

[0149] A phase change-reinforcement-solidification method for the coordinated treatment of high-water content and high-organic matter sludge uses the above-mentioned phosphogypsum-based phase change unfired ceramsite as a raw material for solidified sludge, and other process steps and parameters are the same as those in Example 4.

[0150] A solidified sludge mixed with phosphogypsum-based phase-change unfired ceramsite, using the phosphogypsum-based phase-change unfired ceramsite, comprising the following raw materials in parts by weight:

[0151] 60 parts of sludge (water content 50%, organic matter content 5%), 0.1 parts of potassium ferrate, 3.6 parts of cement, 1.3 parts of phosphogypsum, and 35 parts of the above-mentioned phosphogypsum-based phase-change unfired ceramsite.

[0152] A phase change-reinforcement-solidification method for the coordinated treatment of high-water content and high-organic matter sludge uses the above-mentioned phosphogypsum-based phase change unfired ceramsite as a raw material for solidified sludge, and other process steps and parameters are the same as those in Example 4.

[0153] Example 10

[0154] A phosphogypsum-based phase-change unfired ceramsite, whose raw material composition is the same as that of Example 8.

[0155] A method for preparing phosphogypsum-based phase-change unfired ceramsite, using the above-mentioned raw materials of phosphogypsum-based phase-change unfired ceramsite, and other process steps and parameters are the same as those in Example 8.

[0156] A solidified sludge doped with phosphogypsum-based phase-change unfired ceramsite, using the raw materials of the phosphogypsum-based phase-change unfired ceramsite, includes the following raw materials in parts by weight:

[0157] 80 parts of sludge (water content 50%, organic matter content 5%), 0.1 parts of potassium ferrate, 3.6 parts of cement, 1.3 parts of phosphogypsum, and 35 parts of the above-mentioned phosphogypsum-based phase-change unfired ceramsite.

[0158] A phase change-reinforcement-solidification method for the coordinated treatment of high-water content and high-organic matter sludge uses the above-mentioned phosphogypsum-based phase change unfired ceramsite as a raw material for solidified sludge, and other process steps and parameters are the same as those in Example 4.

[0159] Comparative Example 1

[0160] A solidified sludge, which is different from Example 4 only in that phosphogypsum-based phase-change unfired ceramsite is not included. The remaining raw materials, process steps and parameters are the same as those of Example 4.

[0161] Comparative Example 2

[0162] A solidified sludge, which is different from Example 4 only in that potassium ferrate is not included. The remaining raw materials, process steps and parameters are the same as those of Example 4.

[0163] Application Example 1

[0164] The solidified sludge of the phase-change unfired ceramsite mixed with phospho-gypsum obtained in Example 4 is used as an anti-seepage material for the core wall dam of a high dam in a high-cold area. The application arrangement of the solidified sludge of the phase-change unfired ceramsite mixed with phospho-gypsum in the core wall dam can be seen in the attached figure. Figure 3 The solidified sludge obtained meets the requirements of Article 4.1.6 of the "Design Code for Roller Compacted Earth-Rock Dams" (SL274-2020) on anti-seepage soil materials and can be used as core wall anti-seepage materials. In addition, the solidified sludge has stable engineering properties and has the necessary strength to meet the structural requirements of the core wall dam.

[0165] The silt described in this application example can also be locally sourced from reservoirs / river bed mud in mountainous areas.

[0166] As the construction of earth-rock dams in my country gradually develops towards high dams, high altitude areas and cold regions, the winter construction of high dams in cold regions gradually presents the following two problems:

[0167] On the one hand, during construction at negative temperatures, the compaction performance of the anti-seepage core wall soil is reduced due to freezing. In the project, measures such as covering the surface with geomembrane for insulation, stopping work to prevent freezing, and increasing the number of rolling times are often taken. In addition, since the freezing and thawing of the anti-seepage soil will cause the strength and anti-seepage performance of the anti-seepage body to decrease, the frozen soil will be excavated to a certain depth and refilled during construction, which will increase the construction cost;

[0168] On the other hand, traditional medium and low dams often use pure clay as core wall filling material. For the construction of high earth-rock dams, the difference in modulus between the core wall filling material and the dam shell material will cause uneven settlement, produce an arch effect, and easily cause undesirable phenomena such as cracks and hydraulic fracturing. As a result, it is difficult to meet the requirements by using a single soil material as the core wall anti-seepage material. Therefore, it is necessary to add granular reinforcement materials (such as the phase change expanded clay in this application) for mold enhancement treatment.

[0169] Figure 6 The figure is a schematic diagram comparing the temperature change process lines when the solidified sludge of Example 4 and Comparative Example 1 is used respectively on the junction surface of new and old materials during the construction period of a high dam in a high-cold area in Application Example 1 of the present invention. As shown in the figure, when the temperature drops, the PCM in the solidified sludge of the phosphogypsum-based phase-change unfired ceramsite provided in Example 4 absorbs and stores heat, thereby increasing the minimum temperature of the junction surface of new and old materials at night during the construction period and reducing the part of the material that cannot be constructed due to freezing; in addition, when the ambient temperature changes, the PCM can absorb and release heat through its phase change process to resist it, delay the freezing and thawing process of free water, reduce the freezing and migration of water molecules between particles, further reduce the water absorption and water loss of soil particles, and the swelling and shrinkage of soil particles are also reduced, so the antifreeze performance of the soil material can be improved.

[0170] The two problems mentioned above are particularly prominent during the construction period of the dam. The solidified sludge of the phosphogypsum-based phase-change unfired ceramsite provided in this embodiment can well solve these problems and has the following technical effects:

[0171] Through PCM energy storage, the lowest temperature of the dam construction surface at night is increased, the freezing of soil materials is reduced, the night construction time is extended, the overall construction period of the dam is shortened, and the economic benefits of the project are improved; PCM can regulate the temperature field inside the dam body, reduce the expansion and contraction characteristics of the dam soil, and improve the frost resistance of the core wall anti-seepage filling material; secondly, the solidified sludge of the phosphogypsum-based phase-change unfired ceramsite provided in Example 4 makes full use of the porous and highly adsorbent characteristics of ceramsite to directly adsorb PCM, reducing the cost of using PCM in the project, and the permeability coefficient of the solidified sludge of the phosphogypsum-based phase-change unfired ceramsite does not become very large after multiple freeze-thaw cycles, and is less affected by freeze-thaw cycles, and can maintain good anti-seepage performance and has excellent anti-seepage effect. In addition, the phosphogypsum-based phase-change unfired ceramsite in Example 4, as a particle reinforcement material, plays a reinforcing role in the solidified sludge after rolling, which can improve the strength and modulus of the core wall filling material, reduce the modulus difference between the anti-seepage material and the dam shell, avoid the disaster caused by the "arch effect", and at the same time, it is conducive to the solidified sludge to adapt to the high-intensity all-weather continuous construction of large-scale machinery in high dams.

[0172] Application Example 2

[0173] The application scenario of the solidified sludge of the phospho-gypsum-based phase-change unfired ceramsite obtained in Example 4 being used as a lining channel cushion material, and the application arrangement of the solidified sludge of the phospho-gypsum-based phase-change unfired ceramsite in the lining channel cushion can be seen in the attached Figure 5 .

[0174] Most of the irrigation canals in the cold regions of northern my country are located in seasonally frozen areas. When the temperature drops, the canal foundation soil frosts and deforms. The rigid canal lining is difficult to adapt to the uneven frost deformation of the canal foundation soil and is damaged. This phenomenon seriously affects the normal operation of the canal system and the full realization of the project benefits. In addition, the damage of the lining structure will also lead to a large loss of water resources in the irrigation canal, which runs counter to our current water conservation priority water management policy.

[0175] Figure 7 This is a schematic diagram comparing the temperature variation curves with depth Z when the solidified sludge of Example 4 and Comparative Example 1 are used for the cold region channel cushion in Application Example 2 of the present invention. As shown in the figure, as the depth increases, the temperature gradually changes from negative temperature to positive temperature. The use of PCM can reduce the thickness of the frozen soil layer; in addition, the PCM in the solidified sludge resists the change of ambient temperature through phase change temperature regulation, delays the freezing and thawing of free water between soil particles, reduces the migration of water molecules, reduces the water absorption and loss of soil particles, and thus reduces the swelling and shrinkage of soil particles.

[0176] In this application example, the solidified sludge mixed with phosphogypsum-based phase-change unfired ceramsite is used as a lining channel cushion material, which has the following beneficial effects:

[0177] (1) PCM adsorbed in phosphogypsum-based unfired ceramsite stores and releases heat through phase change process, resists external temperature changes, adjusts the temperature field in the lining structure and channel foundation soil, reduces soil particle expansion and contraction and repeated freezing and thawing of free water, alleviates structural fatigue damage at the micro level, and improves the overall stability of the channel at the macro level;

[0178] (2) The stiffness of the solidified sludge mixed with phosphogypsum-based phase-change unfired expanded clay is between that of the lining structure and the channel subsoil, which can improve the rigid-flexible contact conditions between the two during operation, thereby making the stress distribution of the lining structure uniform and reducing the frost heave damage of the lining structure caused by uneven deformation of the channel subsoil.

[0179] Application Example 3

[0180] The solidified sludge of the phosphogeny-based phase-change unfired ceramsite obtained in Example 8 is used as the wall material of the agricultural greenhouse solar greenhouse. The arrangement of the solidified sludge in the solar greenhouse wall can be seen in the attached Figure 4 The sludge used in this application example can be selected from the bottom mud of the ditch near the construction process of the agricultural greenhouse solar greenhouse.

[0181] According to relevant research, the bottleneck restricting the production efficiency and development speed of solar greenhouses in northern my country has always been the high energy consumption cost. Research on the application of phase change materials in greenhouse heat storage has great practical significance for saving energy, reducing environmental pollution and improving greenhouse production efficiency. Phase change materials used for greenhouse heat storage should meet the conditions required for plant growth in agricultural greenhouses. The suitable growth temperature of general facility crops is 15-23℃, which requires the PCM phase change temperature to be in this range.

[0182] Figure 8 This is a schematic diagram comparing the air temperature change process lines when the solidified sludge in Example 8 and Comparative Example 1 is used respectively during the use period of the agricultural greenhouse solar greenhouse in Application Example 2 of the present invention. As shown in the figure, the PCM in the solidified sludge absorbs and releases heat during its phase change process to resist the external temperature change, slows down the room temperature change rate, reduces the peak temperature in the greenhouse, and narrows the temperature range that is not suitable for crop growth.

[0183] In this application example, the solidified sludge of phase-change unfired ceramsite mixed with phosphogypsum is used as the wall insulation material of agricultural greenhouse solar greenhouse, which has the following beneficial effects:

[0184] (1) PCM adsorbed in phosphate-doped gypsum-based unfired ceramsite can effectively reduce the peak temperature of the greenhouse during the day, increase the minimum temperature in the greenhouse at night, reduce the heating energy consumption at night, save energy, and improve the production efficiency of the solar greenhouse;

[0185] (2) The phosphogenetic gypsum-based phase-change unfired ceramsite embedded in the solidified sludge acts as an aggregate to reinforce the sludge, so that the solidified sludge in this embodiment has a higher strength than the traditional solar greenhouse wall materials (brickwork, plain soil, etc.);

[0186] (3) The bottom mud of the water ditches near the agricultural planting area excavated during the construction of the solar greenhouse was used as wall material, which, to a certain extent, solved the problem of the difficulty in stacking the riverbed mud solid waste;

[0187] (4) The solidified sludge of the phosphate-doped gypsum-based phase-change unfired ceramsite provided by the present invention has better heat storage performance than traditional wall materials, so it can reduce the wall thickness and the amount of traditional materials used, thereby reducing environmental pollution.

[0188] Technical effects:

[0189] 1. The bulk density, cylinder pressure strength and 1h water absorption rate of the phosphogypsum-based unfired ceramsite obtained in Examples 1 to 3 are shown in Table 1:

[0190] Table 1 Experimental data of Examples 1 to 3

[0191]

[0192] It can be seen from Table 1 that the prepared ceramsite can meet the requirements of the specification "Light aggregate and its test method Part 1: Light aggregate" (GB / T 17431.1-2010) for cylinder compressive strength (greater than 0.8 MPa) and water absorption (10% to 20%).

[0193] By comparing Examples 1 to 3, it can be seen that the expanded clay obtained in Example 2 has the largest cylinder compressive strength and the largest water absorption rate, which is beneficial to the subsequent absorption of moisture in the phase change material and sludge. Therefore, it is believed that the ratio used in Example 2 is the optimal ratio.

[0194] 2. The phase change temperature range, 7d unconfined compressive strength and 7d permeability coefficient of the solidified sludge obtained in Examples 4 to 10 and Comparative Examples 1 to 2 are shown in Table 2:

[0195] Table 2 Experimental data of Examples 4 to 10 and Comparative Examples 1 to 2

[0196]

[0197] As shown in Table 2, the permeability coefficient of the silt treated by the silt solidification method proposed in the present invention can meet the requirements of the specification for the design of rolled earth-rock dams (SL274-2020), which stipulates that the permeability coefficient of the anti-seepage soil material of the core wall dam should not be greater than 1×10 -5 cm / s requirement.

[0198] By comparing Examples 4 and 5, it can be seen that increasing the amount of cement can improve the strength and permeability of solidified sludge. From a microscopic perspective, hydration reaction will continue to occur when cement infiltrates into the sludge, and its product has gelling properties, which bonds the particles together and increases the overall strength. In addition, the hydration product will also fill the pores between the particles and improve the anti-seepage performance of the sludge. However, it should be noted that simply increasing the amount of cement is uneconomical.

[0199] By comparing Examples 4 and 6, it can be seen that the strength and permeability of the solidified sludge are improved, but the amount of sludge raw material used in this example is reduced, which can also be understood as improving the strength and permeability by increasing the amount of cement used.

[0200] By comparing Examples 4 and 7, it can be seen that when the amount of sludge increases and the amount of ceramsite decreases, the strength and impermeability of the solidified sludge decrease.

[0201] By comparing Example 4 and Comparative Example 1, it can be seen that when the phosphogypsum-based phase-change unfired ceramsite is lacking in the sludge solidification raw material, the strength is reduced more and the permeability coefficient is also increased. It can be seen that the lack of reinforcement and strengthening of the phosphogypsum-based phase-change unfired ceramsite in the sludge solidification has a relatively large impact on its strength and permeability, which fully demonstrates that the use of the water absorption of the phosphogypsum-based phase-change unfired ceramsite in the present invention to reduce the moisture content of the sludge is conducive to accelerating the sludge solidification process and improving the solidification effect.

[0202] By comparing Example 4 with Comparative Example 2, it can be seen that without the pretreatment step of potassium ferrate on the sludge, the strength of the solidified sludge decreased and the permeability coefficient increased. This shows that the pretreatment of potassium ferrate in the present invention effectively reduces the organic matter content in the sludge and improves the solidification effect.

[0203] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A phosphogypsum-based unfired ceramsite, characterized in that: The invention comprises the following raw materials in parts by weight: 30-45 parts of phosphogypsum, 13-18 parts of fly ash, 13-18 parts of carbide slag, 5-10 parts of vermiculite, 4 parts of hydrogen peroxide and 20 parts of water.

2. The method for preparing phosphogypsum-based unfired ceramsite according to claim 1, characterized in that: The following steps are involved: The phosphogypsum, carbide slag and vermiculite are ground and then mixed with fly ash, and a mixed solution of hydrogen peroxide and water is sprayed while stirring, and then granulated, aged, microwave irradiated and steam cured to obtain phosphogypsum-based unfired ceramsite.

3. The method for preparing phosphogypsum-based unfired ceramsite according to claim 2, characterized in that: The aging time is 2 to 4 hours; The power of the microwave irradiation is 480W and the time is 3min; The temperature of the steam curing is 120-140° C., and the time is not less than 2 days.

4. A method for preparing phosphogypsum-based phase-change unfired ceramsite, characterized in that: The following steps are involved: The phosphogypsum-based unfired ceramsite according to claim 1 is immersed in a liquid phase change material, filtered, and allowed to stand in an environment below the phase change temperature to obtain the phosphogypsum-based phase change unfired ceramsite.

5. The method for preparing phosphogypsum-based phase-change unfired ceramsite according to claim 4, characterized in that: The soaking specifically comprises the following steps: In a vacuum environment with a negative pressure of 50 to 80 kPa, phosphogypsum-based unfired ceramsite is immersed in excess liquid phase change material for 0.5 to 2 hours, and then the vacuum state is eliminated to normal pressure and the immersion is continued for 30 minutes.

6. The phosphogypsum-based phase-change unfired ceramsite prepared by the method for preparing phosphogypsum-based phase-change unfired ceramsite as described in claim 4 or 5.

7. A solidified sludge of phospho-gypsum-based phase-change unfired ceramsite, characterized in that: Including the phosphogypsum-based phase-change unfired ceramsite as described in claim 6.

8. The solidified sludge of the phosphite-doped gypsum-based phase-change unfired ceramsite according to claim 7, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of sludge, 0.1 parts of potassium ferrate, 2.0-3.6 parts of cement, 1.3-2.9 parts of phosphogypsum and 15-35 parts of the phosphogypsum-based phase-change unfired ceramsite.

9. A method for co-disposing high-water content and high-organic matter sludge by phase change-reinforcement-solidification, characterized in that: The raw material of solidified sludge using the phosphogenetic gypsum-based phase-change unfired ceramsite according to claim 7 or 8 specifically comprises the following steps: The sludge is mixed with potassium ferrate and allowed to stand for pretreatment for 24 hours. It is then mixed evenly with cement, phosphogypsum and phosphogypsum-based phase-change unfired ceramsite and allowed to stand for curing to obtain solidified sludge mixed with phosphogypsum-based phase-change unfired ceramsite, thus completing the phase change-reinforcement-solidification coordinated treatment of high-water content and high-organic matter sludge.

10. Use of the solidified sludge of the phosphogeny gypsum-based phase-change unfired ceramsite as claimed in claim 7 or 8 in the field of construction.

Citation Information

Patent Citations

  • Phosphogypsum-sludge combined curing treatment method

    CN101579683A

  • Method for treating sludge with ceramsite

    CN108328900A

  • Multi-solid-waste non-sintered ceramsite based on phosphogypsum and preparation method of multi-solid-waste non-sintered ceramsite

    CN115368041A